'The traveller's guide to health'. Issue 14 (11th July 1988) - Unknown
Abstract : Two attractive and useful new DHSS booklets for travellers abroad outline the preparations to make 'before you go' abroad (SA40) and 'while you're away' (SA41). The first gives a comprehensive guide to the recommended and mandatory vaccinations and guidance on avoiding AIDS and rabies. It also explains how to ensure health care overseas with minimum expense. The second gives advice on how to avoid illness, e.g. diarrhoea, sunburn, malaria, and how to deal with medical emergencies. Copies are available free from pharmacies and travel agents, and by telephone request to 0800 555777.